2016
DOI: 10.1177/0218492316637714
|View full text |Cite
|
Sign up to set email alerts
|

Is delayed surgery related to worse outcomes in native left-sided endocarditis?

Abstract: Delayed surgery is not associated with worse outcomes. Both early and delayed approaches are safe and provide acceptable results. Timing of surgery should be tailored to each patient's clinical status, not based on duration of endocarditis alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…In a recent meta‐analysis, patients operated for left‐sided endocarditis within 7 days after diagnosis had better survival in comparison to patients operated later or managed medically . However, in some retrospective studies, the benefit of ES has been questioned . In our study, even though patients operated within 7 days of prior directed antimicrobial treatment had a higher frequency of acute heart failure and emergency surgery, their 30‐day and late mortality were compared with patients operated later.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In a recent meta‐analysis, patients operated for left‐sided endocarditis within 7 days after diagnosis had better survival in comparison to patients operated later or managed medically . However, in some retrospective studies, the benefit of ES has been questioned . In our study, even though patients operated within 7 days of prior directed antimicrobial treatment had a higher frequency of acute heart failure and emergency surgery, their 30‐day and late mortality were compared with patients operated later.…”
Section: Discussionsupporting
confidence: 61%
“…12 However, in some retrospective studies, the benefit of ES has been questioned. 13,14 In our study, even though patients operated within 7 days of prior directed antimicrobial treatment had a higher frequency of acute heart failure and emergency surgery, their 30-day and late mortality were compared with patients operated later. In the randomized Early Surgery versus Conventional Treatment for Infective endocarditis (EASE) study, surgery within 48 hours for IE was shown to decrease the composite endpoint of death from any cause and embolic events.…”
Section: Discussionmentioning
confidence: 74%
“…In our patients, stroke was associated with a four-times higher risk of death. Although it remains unclear whether early cardiac surgery improves the prognoses of patients, optimal timing seems to be of great importance (34,35). Compared with conventional treatment, an early surgery strategy may be associated with improved clinical outcomes by effectively decreasing systemic embolism in patients with IE (36).…”
Section: In-hospital Mortalitymentioning
confidence: 99%